I have to test whether the following system is invariant or not: $T[x[n]]=\sum_{k=n-1}^{n+2}x[k]$, so I want to verify that, if $y[n]=T[x[n]]$, then $y[n-N]=T[x[n-N]]$. $$T[x[n-N]]=\sum_{k=n-1}^{n+2}x[k-N]$$ $$y[n-N]=\sum_{k=n-N-1}^{n-N+2}x[k]$$ In the first equation, if $k'=k-N$, we have that $T[x[n-N]]=\sum_{k'=n-N-1}^{n-N+2}x[k']$, so both sums are equal and thus the system is invariant. Is this correct or am I making wrong assumptions? Thanks in advance!


Yes your computation is correct. Indeed, you could have seen this even easier, had you considered that the output computation sum was

$$ y[n] = T\{x[n]\} = x[n-1] + x[n] + x[n+1] + x[n+2] .$$

And this is clearly an LTI (linear time-invariant), FIR (finite impulse response) system with associated impulse response

$$h[n] = \delta[n-1] + \delta[n] + \delta[n+1] + \delta[n+2] $$

| improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.